ORIGIN AND SOURCE OF SPRINGS WEST. IRAQ - Al Dahaan, Saadi. (Journal of Kufa-Physics, 2014)
Springs are Creating when the water table intersects the land surface and water flows onto the surface. Springs considered the main water for human living, when the surface water is rare or unavailable. This research is a trial to find the source and origin of Hit-Kubasa city springs (W-Iraq), and the relationship between springs and ground water. Springs are found at the eastern edge of the western desert, and extended to about 20 kilometer from Hit to Kubasa city. Hydrochemistry of the springs Shows high salinity and very hard water. Water type of Hit-Kubasa springs is Mg-Ca-Na-chloride. The origin of sprigs is marine origin. Also the springs are Cl-Ca water type. According to Sulins (1975) classification , water springs reflects the marine origin of water bearing formation and long period of marine deposits, so the marine water have been subjected to different diagenetic processes. Source of Hit-Kubasa springs is marine water that has been left during the deposition.